Motivators for student academic dishonesty at a medium sized university in Alberta, Canada: Faculty and student perspectives - Awosoga, Oluwagbohunmi; Varsanyi, Stephanie; Nord, Christina; Barley, Randall; Meadows, Jeff (Canadian Perspectives on Academic Integrity, 2021)
Academic misconduct describes a complex set of behaviours with many reported motivating factors. However, most research investigating the motivating factors behind academic misconduct has been conducted on American college students. To assess academic misconduct at our mid-sized university in Alberta, Canada, we conducted focus groups with students and faculty to further explore the motivational factors underlying academic misconduct. We conducted a thematic analysis on the interview responses in which two thematic categories of motivations arose: dispositional (or psychological) factors and situational (or contextual) factors. Both student and faculty participants reported a variety of motivating factors for academic misconduct, including but not limited to dispositional aspects, such as attitudes concerning academic misconduct or a lack of understanding, as well as contextual factors, such as taking a full course load and familial pressure. However, unlike their American counterparts, our participants did not discuss the impact that their peers have on motivating academic misconduct. We add our results to the growing body of research which focuses on identifying and analyzing Canadian trends in academic misconduct research.